The Demographics of Molar Pregnancies in BPKIHS - Koirala, A; Khatiwada, P; Giri, A; Kandel, P; Regmi, M; Upreti, D (Kathmandu University Medical Journal, 2012)
This is an analysis of the incidence of molar pregnancies and those of complete and partial molar pregnancies across the reproductive age range for BP Koirala Institute of Health Sciences (BPKIHS) in the period 2010-2011. Patients with molar pregnancies registered with BPKIHS from January 2008 to January 2010 were identified. The overall number of molar pregnancies registered was compared to the number of maternities (live births and still births) and total viable conceptions for this year. A retrospective study of 64 cases of molar pregnancies recorded at BPKIHS during the two year time was done. Medical records were reviewed. Incidence, clinical presentation and methods of diagnosis were studied. During the study period, there were 37 complete moles, 23 partial moles, 1 persistent gestational trophoblastic tumor, 1 choriocarcinoma, and 2 invasive moles. The incidence of molarpregnancy was 3.94 per 1000 deliveries. Median distribution was at 22 years of age, and majority (67%) presented during early second trimester. Twenty one (32.8%) women were of blood group A positive and ten (15.6%) presented with severe form of anemia. This study provides detailed data regarding the incidence of partial and complete molar pregnancies with increasing maternal age. It confirms the relation of molar pregnancy with age, and blood group. Complete mole had the highest incidence, affecting mostly younger age group, and usually in the first half of their pregnancy. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6349 Kathmandu Univ Med J 2011;9(4):298-300